Some invariants for σ-permutation maps - Balibrea, Francisco; Cánovas Peña, Jose S.; López, Víctor Jiménez (Annales Mathematicae Silesianae, 1999)
In this paper we obtain some formulas which allow us to compute topological and metric entropy and topological pressure for a new class of maps. It is also shown that similar formulas do not hold for metric and topological sequence entropy and a new commutativity problem is posed.